A young lady with ANA negative SLE and Secondary Anti Phospholipid Syndrome - Richmond Ronald Gomes; Deepankar Kumar Basak; Kaniz Rahman; Md. Rashidul Hasan (Indonesian Rheumatology Association, 2020)
A B S T R A C TSystemic lupus erythematosus (SLE) is a chronic, inflammatory,autoimmune, multisystem connective multi system connective tissuedisease characterized by various autoantibodies to nuclear and cytoplasmicantigens and commonly affects the joints and a variety of organs due to anover activation of the body's immune system. There is wide heterogeneity inpresentation of SLE patients, including lung, central nervous system, skin,kidney, and hematologic manifestations. The presence of antinuclearantibodies (ANA) in serum is generally considered a decisive diagnostic signof SLE. However, a small subset of SLE patients who had the typical clinicalfeatures of SLE was reported to show persistently negative ANA tests. Ourreport describes a 24-yr-old female who presented with the clinicalmanifestations of SLE such as malar rash, photosensitivity, arthritis, oralulcer, and proteinuria. The serum autoantibodies were all negative exceptanti ribosomal P. She was also positive for lupus anticoagulantanti -coagulant. She was treated with oral prednisolone , hydroxychloroquinewith topical tacrolimus, and improved significantly. Three months after,repeat ANA, and anti-ds DNA showed persistent negativity, but lupus anti -coagulant remained positive. This case suggests that ANA may not berequired in the pathogenesis of SLE.